Critical perspectives on wives : roles, representations, identities, work - O'Brien, Lynn (Demeter Press, 2019)
This interdisciplinary volume opens an innovative space for critical discussion, and production of new imaginaries within, feminist scholarship, analysis and feminist politics, about what is and has been meant by, involved in, required of, and what it means to be, a ""wife."" Contributions within this volume together critically explore and tease out, intersections, overlaps, and distinctions between the social categories of wife and mother, and the link, and separate, labours of wife-work and maternal caregiving labour. This volume brings together diverse critical perspectives through creative.